Vascularisation of Endometrium In Primary Dysmenorrhea wsr to Kha-Vaigunya (International Journal of Ayurveda and Pharma Research, 2023)
Painful menstruation can be correlated with Udavartini Yonivyapad in Charaka Samhita or Udavarta Yonivyapad in Susruta Samhita. Deregulation of endometrial blood flow has been associated with several menstrual disorders including primary dysmenorrhoea, menorrhagia, inter-menstrual bleeding and endometriosis. Doppler assessment of uterine artery is essential to reflect endometrial vascularisation. It is identified that pain in primary dysmenorrhea is caused by excessive endometrial prostaglandin production leading to abnormal uterine activity and consequent changes in blood flow within the uterus. Kha vaigunya is a process with a general cause for abnormalities in the Srothas (vasculature). It is a gradually progressing chronic phenomenon which may lead to an interruption in circulation of materials causing the physiological arrest of metabolism and the elimination of metabolic wastes. Therefore excessive production of the metabolic materials leads to excessive amounts of prostaglandin. The aim of this study was to explore the relationship between pain and uterine vascularity and the study suggests that primary dysmenorrheaic patients tend to have moderately positive correlation with pain intensity.